Desenvolvimento de membranas poliméricas enantiosseletivas utilizando partículas tipo-Pirkle para resolução de compostos quirais - Vedovello, Priscila (2023)
The formation of chiral compounds during the synthesis of new drugs and other substances, which are administered clinically in the form of racemic mixture, is amply described in the literature. The therapeutic activity of these compounds is strongly dependent on their spatial rearrangements, leading to different pharmacodynamic and pharmacokinetic properties, in which one isomer may produce the desired therapeutic activities, while the other may be inactive or even produce toxic effects. Alternatives to bypassing the formation of chiral compounds include stereoselective synthesis and post-synthesis separation. This work aimed to develop low-cost hybrid polymeric membranes with high chiral resolution capability. Mesoporous materials (MCM-41) obtained from rice husk biomass by the hydrothermal method and by the post-synthesis grafting method were evaluated for their chiral selection capacity. Pirkle-type selectors were grafted into MCM-41 and these materials were incorporated in a polymeric membrane. The Pirkle-type chiral selector was characterized by thermogravimetric analysis (TGA), nuclear magnetic resonance, 1H NMR and 13C NMR and Fourier transform infrared spectroscopy (FTIR) to confirm the structure. The samples were characterized by FTIR and nitrogen adsorption-desorption. MCM-41 exhibited type IV isotherms and type H1 hysteresis, good thermal stability, uniform mesopore size distribution, and high surface area. The functionalization of MCM-41 caused a decrease in the surface area, observed by the technique of adsorption-desorption of N2. FTIR and nitrogen adsorption-desorption analysis, confirmed the presence of Pirkle-type selectors within the MCM-41 structure. MCM-41-Pirkle membranes showed preferential retention activity over one enantiomer, (S)-Pirkle Alcohol. MCM-41-Pirkle membranes showed good permeation enantioselectivity (α = 1.28) when compared to other studies. The membranes containing MCM-41-(S,S)-Whelk-O®1 showed excellent retention for the xanthonic compound XEA, with a high permeation selectivity compared to the other selector tested (α = 16.78). As evidenced by permeation and sorption assays of different enantiomeric compounds, this study demonstrates that membranes containing mesoporous materials anchored with chiral selectors can be an effective tool for the separation of enantiomers.